Changing nitrogen deposition with low δ15N−NH4+ and δ15N−NO3− values at the Experimental Lakes Area, northwestern Ontario, Canada - J.J. Venkiteswaran; S.L. Schiff; M.J. Paterson; N.A.P. Flinn; H. Shao; R.J. Elgood (Canadian Science Publishing, 2017)
Ammonium deposition at the International Institute for Sustainable Development Experimental Lakes Area (IISD-ELA), in northwestern Ontario, Canada, has doubled in the last 45 years and thus is no longer among the low nitrogen (N) deposition sites in North America. This may be related to the concurrent intensification of Manitoba agriculture to the west and upwind of the ELA. Large increases in ammonium deposition at the ELA were important in driving the observed trend and increased the NH4 + to NO3 − ratio of input to aquatic and terrestrial systems. Stable isotope analyses of two years of bulk (wet and dry) atmospheric deposition revealed very large ranges in δ15N−NH4 + (22‰ range), δ15N−NO3 − (18‰), and δ18O-NO3 − (19‰). Few other δ15N−NH4 +, δ15N−NO3 −, and δ18O-NO3 − values have been published for Canadian precipitation. Increases in δ15N of NH4 + and NO3 − in July occurred with increases in total N deposition. The wide range and seasonal trends of δ15N and δ18O values in ELA precipitation mean that studies characterizing N inputs to watersheds and lakes require an ongoing and comprehensive annual sampling regime. Global trends of declining δ15N of N deposition evident in lake sediment records may be a result of increases in NH4 + deposition with lower δ15N−NH4 + values. Similarly, the relationship in Lake Superior between increasing NO3 − and lower δ15N−NO3 − values may be explained by increased atmospheric deposition of N with low δ15N values.